Banana peels sorbent : An alternative activated carbon material for food dye reduction in aqueous - Noor Yahida, Yahya; Aniq Amirah, Kamarruzaman; Nurul Hafeeza, Mohamed (2021)
Today, the most commonly adopted adsorbent is Activated Carbon. It has large surface area, excellent porosity, low density with high adsorption efficiency towards contaminants in aqueous solution. Besides that, this carbonaceous material has high physicochemical stability, mechanical strength and degree of surface reactivity, with large surface area responsible for the efficiency of adsorption reaction mechanism. Generally, it is derived from coal, a non-renewable carbon source with a relatively high price. Therefore, with an economic point of view, researchers have made extensive efforts to find a low-cost alternative material for Activated Carbon preparation from a range of lignocellulosic materials, biopolymer, coal, char, and fruit peels. Therefore, we have come out with a solution of Banana Peels as the potential material for Activated Carbon preparation.